2010
DOI: 10.1007/s13238-010-0101-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of four novel DC-SIGN ligands on Mycobacterium bovis BCG

Abstract: Dendritic-cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN; CD209) has an important role in mediating adherence of Mycobacteria species, including M. tuberculosis and M. bovis BCG to human dendritic cells and macrophages, in which these bacteria can survive intracellularly. DC-SIGN is a C-type lectin, and interactions with mycobacterial cells are believed to occur via mannosylated structures on the mycobacterial surface. Recent studies suggest more varied modes of binding to multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…( C ) Listed are the human PRRs activated by Candida and Mycobacteria spp, alongside their cognate PAMPs from each pathogen class. The superscript number(s) next to each mycobacterial PAMP indicates a corresponding reference that documents its association with or activation of TLR2 245–247 , TLR4 248 , TLR6 249 , TLR9 250 , NOD2 251 , MINCLE 252 , MARCO 253 , Dectin-2 254 , Dectin-3 255 , Mannose Receptor 256,257 , CR 258,259 , DC-SIGN 260,261 , Galectin-3 262,263 , CD36 264 , MBL 265 , Dectin-1 266 , NLRP3 267 . The superscript number(s) next to each Candida PAMP indicates a corresponding reference that documents its activation of either TLR2 268270 , TLR4 269,270 , Dectin-1 271 , Mannose Receptor 269 , Dectin-2 272,273 , DC-SIGN 274 , Galectin-3 275 , MINCLE 276 , SCARF1 277 , CD36 277 , MBL 278 , CR3 279 , Dectin-3 280 , TLR9 281,282 , NLRP3 283 , NOD2 282 .…”
Section: Figurementioning
confidence: 99%
“…( C ) Listed are the human PRRs activated by Candida and Mycobacteria spp, alongside their cognate PAMPs from each pathogen class. The superscript number(s) next to each mycobacterial PAMP indicates a corresponding reference that documents its association with or activation of TLR2 245–247 , TLR4 248 , TLR6 249 , TLR9 250 , NOD2 251 , MINCLE 252 , MARCO 253 , Dectin-2 254 , Dectin-3 255 , Mannose Receptor 256,257 , CR 258,259 , DC-SIGN 260,261 , Galectin-3 262,263 , CD36 264 , MBL 265 , Dectin-1 266 , NLRP3 267 . The superscript number(s) next to each Candida PAMP indicates a corresponding reference that documents its activation of either TLR2 268270 , TLR4 269,270 , Dectin-1 271 , Mannose Receptor 269 , Dectin-2 272,273 , DC-SIGN 274 , Galectin-3 275 , MINCLE 276 , SCARF1 277 , CD36 277 , MBL 278 , CR3 279 , Dectin-3 280 , TLR9 281,282 , NLRP3 283 , NOD2 282 .…”
Section: Figurementioning
confidence: 99%
“…Infection studies with (human) DC-SIGN transgenic mice revealed that the lectin’s interaction with Mtb may likely serve as a strategy for host protection against Mtb -mediated tissue pathology and thus provide an environment of Mtb persistence as opposed to simply diminishing host immunity and favoring infection [19]. In addition to ManLAM, several other Mtb ligands such as the mannosylated 19 kDa (LpqH) lipoprotein, DnaK, the 45 kDa (alanine/proline-rich antigen, Apa) glycoproteins and hexamannosylated phosphatidyl- myo -inositol mannosides (PIM 6 ) have been proposed to bind DC-SIGN [5,2224]. We thus sought to determine whether the GalN substituent on AG alters overall interaction of Mtb with DC-SIGN.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria were labeled with MoAb specific for LAM [20], 19 kDa protein [25], DnaK [24], and the 45–47 kDa antigen (Apa) [26]. Mouse MoAbs bound to Mtb were fluorescently labeled with a secondary Alexa fluor 488-conjugated anti-mouse IgG antibody and the geometric MFI was determined by flow cytometry (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…SodA was detected as the major product of the 25-kDa langerin-reactive protein spots, and GroEL1 (presumably as degradation products of this protein) was detected in both the 28-and 25-kDa protein spots. SodA has been reported to specifically bind to surface of human respiratory epithelial cells (30), and M. bovis GroEL1 was shown to be DC-SIGN ligands (31). Although bioinformatics indicated that these two proteins are not glycosylated, their possible interaction with langerin in a carbohydrate-independent manner cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%